Lychee propagation (Litchi chinensis Sonn.): A comparative study of rootstocks - Zaccaro, R. P. (2011)
The lychee (Litchi chinensis Sonnerat), of the family Sapindaceae, is a highly valued fruit throughout the world. It is native to southern China, but it is cultivated in many parts of the world. In Brazil, the cultivation of the lychee was initiated in the 1970s in the State of São Paulo and has been increasing in production even though the crop size still averages only 1.4 ha per producer. The low crop size is attributed to the high cost of seedlings and the amount of time required for the plant to bear fruit. These factors discourage planting in large areas. The purpose of this research is to study some aspects of what is vitally important for the production of lychee seedlings on a large scale, with low cost and good genetic quality. Tests were performed using rootstocks from seeds of lychee and longan (Euphoria longan Lam.). Scions for grafting were taken from plants of lychee 'Bengal' in the collection of fruit species from FCAV-UNESP, Campus of Jaboticabal, Brazil. The experiments were started in September 2007 and the grafting process was performed in each month of the year finishing in August 2008. During this period the influence of these criteria were evaluated: 1) time of the year; 2) species of rootstock; 3) percentage of grafting success; 4) stem height at grafting point; 5) stem diameter at grafting point. Therefore, through statistical analysis we obtained significant differences in relation to the rootstock used, the months of the year in which the grafting was performed and the interaction between rootstock and the month in which the grafting was performed.